Modified hexagonal boron nitride compound as well as preparation method and application thereof

By combining the alkylated alumina microspheres and hydroxylated hexagonal boron nitride nanosheets, a modified hexagonal boron nitride composite is solved, and the problem of uneven dispersion of hexagonal boron nitride microsheets in polymer-based composite materials is achieved, and the thermal conductivity is significantly improved and the material dispersion is improved.

CN119708638APending Publication Date: 2025-03-28YANTAI ADVANCED MATERIALS & GREEN MFG SHANDONG PROVINCIAL LAB +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311248659.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The hexagonal boron nitride micro-nanosheets are unevenly dispersed in polymer-based composite materials, resulting in limited thermal reinforcement effect. In industrial production, there are problems such as unstable product quality, large waste production, low yield and low yield.

Method used

By combining the alkylated alumina microspheres with hydroxylated hexagonal boron nitride nanosheets, the adsorption of the alkylated alumina microspheres and the coating effect of the hydroxylated hexagonal boron nitride nanosheets is used to form a modified hexagonal boron nitride composite, which improves its dispersion and thermal conductivity in the polymer matrix.

Benefits of technology

The modified hexagonal boron nitride composite is not prone to agglomeration, which improves the dispersion in the polymer matrix, builds a phonon transfer channel, enhances the thermal conductivity of the material, reduces the interface thermal resistance, and improves the overall thermal conductivity of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708638A_ABST
    Figure CN119708638A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of heat-conducting fillers, and particularly relates to a modified hexagonal boron nitride compound as well as a preparation method and application thereof. The modified hexagonal boron nitride compound provided by the invention comprises alkylated aluminum oxide microspheres and hydroxylated hexagonal boron nitride nanosheets coated on the surfaces of the alkylated aluminum oxide microspheres. The alkylated aluminum oxide microspheres are combined with the hydroxylated hexagonal boron nitride nanosheets through an adsorption effect, so that the hydroxylated hexagonal boron nitride nanosheets coat the surfaces of the alkylated aluminum oxide microspheres in a lap joint manner, and the dispersity of the modified hexagonal boron nitride is improved. The hydroxylated hexagonal boron nitride nanosheets which are mutually lapped can construct a phonon transmission channel, so that smooth transmission of phonons is facilitated, and the heat conductivity coefficient of the material is improved; meanwhile, on the basis that the original structure of the alkylated alumina microspheres is kept unchanged, dense accumulation among particles can be promoted, and a well-connected heat conduction network is formed, so that the interface thermal resistance is reduced, and the heat conductivity coefficient of the material is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal conductive fillers, and in particular relates to a modified hexagonal boron nitride composite and a preparation method and application thereof. Background Art

[0002] The thermal conductivity of hexagonal boron nitride (h-BN) micro-nanomaterials is completely determined by phonons. For hexagonal boron nitride nanosheets (h-BNNSs), both theory and experiment have shown that the thermal conductivity of h-BNNSs increases with decreasing thickness, which is due to the reduction of Umklapp scattering in thinner h-BNNSs. Theoretical calculations show that the theoretical thermal conductivity of h-BNNSs can reach 1700-2000 W / (m·K). At the same time, h-BN has an electrical insulation band gap of 5.8 eV and excellent electrical insulation properties, with a breakdown field strength of up to 35 kV / mm. Therefore, h-BNNSs is the best filler for preparing high thermal conductivity insulating polymer-based composites. However, the chemical inertness and interlayer van der Waals interactions of h-BN make it difficult to disperse uniformly in the polymer matrix. When the filler content increases, there is a serious interfacial incompatibility between the polymer and the filler interface, resulting in interfacial thermal resistance, leading to the formation of an inhomogeneous structure and limiting the thermal conductivity enhancement effect. At present, the dispersibility of h-BNNSs is mainly improved by preparing h-BNNSs with regular size and thin thickness, but this method is limited to the laboratory and the preparation scale is limited to small batches or even trace levels. Although these methods can prepare h-BNNSs with good product morphology and performance in the laboratory, problems such as unstable product quality, large amount of waste generated, low yield and low yield appear in scale-up experiments and industrial production, and still cannot completely solve the problem of uneven dispersion of hexagonal boron nitride micro-nanosheets in polymer-based composites. Summary of the invention

[0003] In view of this, the present invention provides a modified hexagonal boron nitride composite and a preparation method and application thereof. The modified hexagonal boron nitride composite provided by the present invention is not prone to agglomeration and has improved dispersibility in a polymer matrix.

[0004] In order to solve the above technical problems, the present invention provides a modified hexagonal boron nitride composite, comprising alkylated alumina microspheres and hydroxylated hexagonal boron nitride nanosheets coated on the surface of the alkylated alumina microspheres.

[0005] Preferably, the mass ratio of the alkylated alumina microspheres to the hydroxylated hexagonal boron nitride nanosheets is 0.8-1.2:1.

[0006] The present invention also provides a method for preparing the modified hexagonal boron nitride composite described in the above technical solution, comprising the following steps:

[0007] The hexagonal boron nitride nanosheets and the alkaline solution are mixed and then ball-milled to obtain hydroxylated hexagonal boron nitride nanosheets;

[0008] The silane coupling agent and the ethanol aqueous solution are mixed and the pH value of the mixed system is adjusted to 3 to 7 to obtain an alkylation modified solution;

[0009] The alumina microspheres and the alkylation modification solution are mixed and heated to obtain alkylated alumina microspheres;

[0010] The hydroxylated hexagonal boron nitride nanosheets and alkylated alumina microspheres are dispersed in an acidic solution for coating to obtain the modified hexagonal boron nitride composite.

[0011] Preferably, the plane size of the hexagonal boron nitride nanosheets is 100 nm to 50 μm;

[0012] The pH value of the alkaline solution is 7.1 to 14;

[0013] The mass ratio of the hexagonal boron nitride nanosheets to the volume ratio of the alkaline solution is 1 g:4-6 mL.

[0014] Preferably, the rotation speed of the ball mill is 50 to 400 rpm, and the time of the ball mill is 0.5 to 36 h.

[0015] Preferably, the mass concentration of the ethanol aqueous solution is above 95%;

[0016] The mass percentage of the silane coupling agent in the alkylation modification solution is 0.1-20%.

[0017] Preferably, the average diameter of the alumina microspheres is 100 nm to 50 μm;

[0018] The mass ratio of the alumina microspheres to the alkylsilane coupling agent is 0.1 to 10:1.

[0019] Preferably, the heating treatment is performed at a temperature of 20 to 100° C. and for a time of 0.5 to 20 hours.

[0020] Preferably, the mass ratio of the hydroxylated hexagonal boron nitride nanosheets to the alkylated alumina microspheres is 0.1 to 10:1;

[0021] The coating is accompanied by stirring, the stirring is magnetic stirring, and the time of the magnetic stirring is 0.5 to 20 hours.

[0022] The present invention also provides the use of the modified hexagonal boron nitride composite described in the above technical solution or the modified hexagonal boron nitride prepared by the preparation method described in the above technical solution as a thermal conductive filler.

[0023] The present invention provides a modified hexagonal boron nitride composite, comprising alkylated alumina microspheres and hydroxylated hexagonal boron nitride nanosheets coated on the surface of the alkylated alumina microspheres. In the present invention, the alkylated alumina microspheres are combined with the hydroxylated hexagonal boron nitride nanosheets through adsorption to coat multiple hydroxylated hexagonal boron nitride nanosheets on the surface of the alkylated alumina microspheres in an overlapping manner, thereby improving the dispersibility of the modified hexagonal boron nitride in the polymer matrix. The overlapping hydroxylated hexagonal boron nitride nanosheets can construct a channel for phonon transmission, which is conducive to the smooth transmission of phonons, thereby improving the thermal conductivity of the material; at the same time, the alkylated alumina microspheres have a synergistic enhancement effect on heat conduction. On the basis of maintaining their original structure unchanged, they can promote dense accumulation between particles to form a well-connected heat conduction network, thereby reducing interfacial thermal resistance and further improving the thermal conductivity of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a SEM image of the modified hexagonal boron nitride nanosheet composite prepared in Example 1;

[0025] Figure 2 The infrared spectrum of the composite of hydroxylated hexagonal boron nitride micro-nanosheets, alumina microspheres, alkylated alumina microspheres and modified hexagonal boron nitride nanosheets in Example 1;

[0026] Figure 3 This is a columnar comparison chart of thermal conductivity of thermally conductive silicone grease doped with different mass modified hexagonal boron nitride nanosheet composites. DETAILED DESCRIPTION

[0027] The present invention provides a modified hexagonal boron nitride composite, comprising alkylated alumina microspheres and hydroxylated hexagonal boron nitride nanosheets coated on the surface of the alkylated alumina microspheres. In the present invention, the mass ratio of the alkylated alumina microspheres to the hydroxylated hexagonal boron nitride nanosheets is preferably 0.1 to 10:1, more preferably 1 to 5:1, and further preferably 1:1.

[0028] The present invention also provides a method for preparing the modified hexagonal boron nitride composite described in the above technical solution, comprising the following steps:

[0029] The hexagonal boron nitride nanosheets and the alkaline solution are mixed and then ball-milled to obtain hydroxylated hexagonal boron nitride nanosheets;

[0030] The silane coupling agent and the ethanol aqueous solution are mixed and the pH value of the mixed system is adjusted to 3 to 7 to obtain an alkylation modified solution;

[0031] The alumina microspheres and the alkylation modification solution are mixed and heated to obtain alkylated alumina microspheres;

[0032] The hydroxylated hexagonal boron nitride nanosheets and alkylated alumina microspheres are dispersed in an acidic solution for coating to obtain the modified hexagonal boron nitride composite.

[0033] The present invention mixes hexagonal boron nitride nanosheets and an alkaline solution and then ball mills them to obtain hydroxylated hexagonal boron nitride nanosheets. In the present invention, the mixing process preferably also includes: dispersing the hexagonal boron nitride nanosheets in water. In the present invention, the planar size of the hexagonal boron nitride nanosheets is preferably 100nm to 50μm, more preferably 1 to 40μm. In the present invention, the planar size of the hexagonal boron nitride nanosheets is specifically 0.1μm, 0.5μm, 1μm, 10μm, 30μm, 40μm or 50μm. In the present invention, the mass ratio of the hexagonal boron nitride nanosheets to water is preferably 1:500 to 20:80, more preferably 20:80.

[0034] In the present invention, the dispersion is preferably carried out under ultrasonic conditions, and the power of the ultrasound is preferably 50 to 5000 W, more preferably 100 to 4000 W. In the present invention, the power of the ultrasound is specifically 50 W, 100 W, 200 W, 300 W, 400 W, 500 W, 1000 W, 1500 W, 2000 W, 2500 W, 3000 W, 3500 W, 4000 W, 4500 W or 5000 W. In the present invention, the hexagonal boron nitride nanosheets are first dispersed in water and then mixed with an alkaline solution, which is conducive to full contact between the hexagonal boron nitride nanosheets and the alkaline solution.

[0035] In the present invention, the pH value of the alkaline solution is preferably 7.1 to 14, more preferably 8 to 9. In the present invention, the pH value of the alkaline solution is specifically 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5 or 14.0. The present invention has no special limitation on the type of the alkaline solution, as long as the required pH value can be reached. In an embodiment of the present invention, the alkaline solution is a sodium hydroxide solution with a molar concentration of 5 mol / L. In the present invention, the mass ratio of the hexagonal boron nitride nanosheets to the volume ratio of the alkaline solution is preferably 1g:4 to 6mL, more preferably 1g:5mL.

[0036] In the present invention, the rotation speed of the ball mill is preferably 50 to 400 rpm, more preferably 100 to 300 rpm. In the present invention, the rotation speed of the ball mill is specifically 50 rpm, 80 rpm, 100 rpm, 200 rpm, 5300 rpm or 400 rpm. In the present invention, the time of the ball mill is preferably 0.5 to 36 h, more preferably 8 to 20 h. In the present invention, the time of the ball mill is specifically 0.5 h, 1 h, 4 h, 8 h, 12 h, 16 h, 20 h, 24 h, 28 h, 32 h or 36 h. In the present invention, the environment of the ball mill is preferably normal pressure and normal temperature; the normal pressure is preferably atmospheric pressure, and the normal temperature is preferably room temperature; the temperature of the room temperature is preferably 20 to 35 ° C, more preferably 25 to 30 ° C.

[0037] The invention performs ball milling in an alkaline solution, and hydroxyl groups are grafted onto the edges of hexagonal boron nitride nanosheets.

[0038] The present invention mixes a silane coupling agent and an ethanol aqueous solution, and then adjusts the pH value of the mixed system to 3 to 7 to obtain an alkylated modified solution. In the present invention, the silane coupling agent is preferably KH550. In the present invention, the mass concentration of the ethanol aqueous solution is preferably 95% or more, and more preferably 95 to 98%. In the present invention, the mass percentage of the silane coupling agent in the alkylated modified solution is preferably 0.1 to 20%, and more preferably 1 to 19%. In the present invention, the mass percentage of the silane coupling agent in the alkylated modified solution is specifically 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.

[0039] The present invention selects ethanol aqueous solution as solvent to dissolve the silane coupling agent, and also facilitates the subsequent dispersion of alumina microspheres in the alkylation modification solution. The present invention limits the mass percentage of the silane coupling agent in the alkylation modification solution to the above range to facilitate the hydrolysis reaction of the silane coupling agent.

[0040] In the present invention, the pH value of the mixed system is 3 to 7, preferably 5 to 6; specifically 4.5, 5, 5.5, 6, 6.5 or 7. The present invention has no particular limitation on the pH adjuster used to adjust the pH value of the mixed system, as long as the desired pH value can be achieved. In an embodiment of the present invention, the pH adjuster is preferably acetic acid.

[0041] After obtaining the alkylation modification solution, the present invention mixes the alumina microspheres and the alkylation modification solution and performs a heat treatment to obtain alkylated alumina microspheres. The present invention preferably dries the alumina microspheres before mixing. In the present invention, the drying is preferably oven drying, and the oven drying temperature is preferably 50 to 120°C, more preferably 60 to 80°C. In the present invention, the oven drying temperature is specifically 65°C, 70°C or 75°C. In the present invention, the oven drying time is preferably 6 to 48h, more preferably 12 to 36h. In the present invention, the oven drying time is specifically 6h, 12h, 14h, 16h, 18h, 20h, 24h, 28h, 32h, 36h, 40h or 48h. The present invention can remove moisture from the surface of alumina after drying.

[0042] In the present invention, the average diameter of the alumina microspheres is preferably 100 nm to 50 μm, more preferably 1 to 45 μm. In the present invention, the average diameter of the alumina microspheres is specifically 0.1 μm, 1 μm, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 45 μm.

[0043] In the present invention, the mass ratio of the alumina microspheres to the alkylsilane coupling agent is preferably 0.1 to 10: 1, more preferably 1 to 5: 1. In the present invention, the mass ratio of the alumina microspheres to the alkylsilane coupling agent is specifically 0.5: 1, 1: 1, 1.5: 1, 2: 1, 2.5: 1, 3: 1, 3.5: 1, 4: 1, 4.5: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1 or 1: 1.

[0044] The present invention has no particular limitation on the mixing, as long as it can be mixed evenly. In the present invention, the temperature of the heat treatment is preferably 20 to 100°C, more preferably 35 to 90°C, and further preferably 40 to 60°C. In the present invention, the temperature of the heat treatment is specifically 35°C, 45°C, 55°C, 65°C, 75°C, 85°C or 90°C. In the present invention, the time of the heat treatment is preferably 0.5 to 20h, more preferably 1.5 to 10h. In the present invention, the time of the heat treatment is specifically 1.5h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h.

[0045] In the present invention, the hydrolysis product of the silane coupling agent is connected to the surface of the alumina microspheres through heating treatment.

[0046] In the present invention, the heat treatment preferably further comprises: subjecting the system after the heat treatment to solid-liquid separation, and then washing the solid obtained by the solid-liquid separation with an ethanol aqueous solution to obtain the alkylated alumina microspheres. In the present invention, the solid-liquid separation is preferably filtration, and the filtration is preferably suction filtration; in the present invention, the filter membrane for filtration is preferably an organic filter membrane. In the present invention, the mass concentration of the ethanol aqueous solution is preferably 95% or more, and more preferably 95-98%.

[0047] After obtaining hydroxylated hexagonal boron nitride nanosheets and alkylated alumina microspheres, the present invention disperses the hydroxylated hexagonal boron nitride nanosheets and alkylated alumina microspheres in an acidic solution for coating to obtain the modified hexagonal boron nitride composite. In the present invention, the mass ratio of the hydroxylated hexagonal boron nitride nanosheets and the alkylated alumina microspheres is preferably 0.1 to 10:1, more preferably 2 to 8:1. In the present invention, the mass ratio of the hydroxylated hexagonal boron nitride nanosheets and the alkylated alumina microspheres is specifically 0.1:1, 0.5:1, 1.0:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 9.5:1. In the present invention, the pH value of the acidic solution is preferably 1 to 7, more preferably 4.5 to 6. In the present invention, the pH value of the acidic solution is specifically 1.0, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5 or 7.0.

[0048] In the present invention, the coating process is accompanied by stirring, and the stirring is preferably magnetic stirring, and the time of the magnetic stirring is preferably 0.5 to 20 hours, and more preferably 8 to 15 hours. In the present invention, the time of the magnetic stirring is specifically 1.5 hours, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours. In the present invention, the coating environment is preferably normal pressure and normal temperature; the normal pressure is preferably atmospheric pressure, and the normal temperature is preferably room temperature; the room temperature is preferably 20 to 35°C, and more preferably 25 to 30°C.

[0049] In the present invention, after the coating, the method preferably further comprises: performing solid-liquid separation on the coated system to obtain the modified hexagonal boron nitride composite. In the present invention, the solid-liquid separation is preferably filtering.

[0050] After surface modification of hexagonal boron nitride micro-nano sheets and alumina microspheres respectively, the hydroxylated hexagonal boron nitride micro-nano sheets are effectively, evenly and firmly coated on the surface of the alkylated alumina microspheres through adsorption, which not only solves the problem that the hexagonal boron nitride micro-nano sheets are very easy to agglomerate, but also realizes the effective construction of heat conduction channels, which can greatly improve the thermal conductivity of the polymer matrix; at the same time, the modified hexagonal boron nitride composite can act as a protective layer, reduce the penetration of corrosive ions, and improve the anti-corrosion performance of the polymer material.

[0051] The present invention also provides the use of the modified hexagonal boron nitride composite described in the above technical solution or the modified hexagonal boron nitride prepared by the preparation method described in the above technical solution as a thermally conductive filler. In the present invention, the thermally conductive filler is preferably a thermally conductive filler of a polymer matrix or a thermally conductive filler of a 5G device; the 5G device is preferably a chip. In the present invention, the polymer matrix preferably includes thermally conductive silicone grease or silicone rubber.

[0052] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0053] Example 1

[0054] Hexagonal boron nitride micro-nano sheets with a plane size of 0.5 μm are ultrasonically dispersed in water at a power of 500 W to obtain a hexagonal boron nitride micro-nano sheet dispersion, wherein the mass ratio of the hexagonal boron nitride micro-nano sheets to water is 20:80; the boron nitride nanosheet dispersion and an alkaline solution are mixed and ball-milled to obtain hydroxylated hexagonal boron nitride nanosheets; the alkaline solution is a sodium hydroxide solution with a molar concentration of 5 mol / L and a pH value of 9.7, the mass ratio of the hexagonal boron nitride nanosheets to the alkaline solution is 1 g:5 mL, the ball milling speed is 400 rpm, and the ball milling time is 8 h;

[0055] The silane coupling agent KH550 and an ethanol aqueous solution with a mass concentration of 95% were mixed, and the pH value was adjusted with acetic acid to obtain an alkylation modified solution with a pH value of 5 and a mass concentration of 2% of the silane coupling agent;

[0056] Alumina microspheres with an average diameter of 5 μm were dried in an oven at 65° C. for 10 h; the dried alumina microspheres and the alkylation modification solution were mixed and heated at 60° C. for 4 h; the heated system was filtered using an organic filter membrane, and the filtered solid was washed with an ethanol aqueous solution with a mass concentration of 95% to obtain alkylated alumina microspheres; wherein the mass ratio of the dried alumina microspheres to KH550 in the alkylation modification solution was 1:1;

[0057] Alkylated alumina microspheres, hydroxylated hexagonal boron nitride micro-nanosheets and acetic acid solution are mixed to obtain a mixed system with a pH value of 4.5. The mixed system is magnetically stirred for 8 hours and then filtered to obtain a modified hexagonal boron nitride nanosheet composite; wherein the mass ratio of the alkylated alumina microspheres to the hydroxylated hexagonal boron nitride micro-nanosheets is 2.

[0058] Figure 1 This is the SEM image of the modified hexagonal boron nitride nanosheet composite. It can be seen from the figure that the hexagonal boron nitride micro-nanosheets are effectively, uniformly and firmly coated on the surface of the alumina microspheres, which is consistent with the relevant characteristics of hexagonal boron nitride micro-nanosheets coated with alumina microspheres.

[0059] The hexagonal boron nitride micro-nanosheets, alumina microspheres, alkylated alumina microspheres and modified hexagonal boron nitride nanosheets in Example 1 were subjected to infrared detection to obtain an infrared spectrum, as shown in FIG. Figure 2 As shown. Figure 2 It can be seen that the hydroxylated hexagonal boron nitride nanosheets are wrapped on the surface of the alkylated alumina microspheres to form a modified hexagonal boron nitride nanosheet composite.

[0060] In terms of mass percentage, the modified hexagonal boron nitride nanosheet composite prepared in Example 1 was added to the thermal grease at doping amounts of 0%, 10%, 15% and 20%, and then its thermal conductivity was tested using a thermal conductivity tester. The results are listed in Table 1.

[0061] Table 1 Thermal conductivity of thermally conductive silicone grease doped with different mass modified hexagonal boron nitride nanosheet composites

[0062]

[0063] Draw a bar chart based on Table 1, such as Figure 3 Combining Table 1 and Figure 3 It can be seen that adding the modified hexagonal boron nitride nanosheet composite prepared in the embodiment to different thermal conductive silicone greases can improve the thermal conductivity of the material, and the thermal conductivity increases with the increase of the added amount. The thermal conductivity with an added amount of 20% is much higher than the thermal conductivity of the sample without adding filler.

[0064] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A modified hexagonal boron nitride composite, characterized in that: The invention comprises alkylated alumina microspheres and hydroxylated hexagonal boron nitride nanosheets coated on the surfaces of the alkylated alumina microspheres.

2. The modified hexagonal boron nitride composite according to claim 1, characterized in that: The mass ratio of the alkylated alumina microspheres to the hydroxylated hexagonal boron nitride nanosheets is 0.8-1.2:

1.

3. The method for preparing the modified hexagonal boron nitride composite according to claim 1 or 2, characterized in that: The following steps are involved: The hexagonal boron nitride nanosheets and the alkaline solution are mixed and then ball-milled to obtain hydroxylated hexagonal boron nitride nanosheets; The silane coupling agent and the ethanol aqueous solution are mixed and the pH value of the mixed system is adjusted to 3 to 7 to obtain an alkylation modified solution; The alumina microspheres and the alkylation modification solution are mixed and heated to obtain alkylated alumina microspheres; The hydroxylated hexagonal boron nitride nanosheets and alkylated alumina microspheres are dispersed in an acidic solution for coating to obtain the modified hexagonal boron nitride composite.

4. The preparation method according to claim 3, characterized in that: The plane size of the hexagonal boron nitride nanosheets is 100nm to 50μm; The pH value of the alkaline solution is 7.1 to 14; The mass ratio of the hexagonal boron nitride nanosheets to the volume ratio of the alkaline solution is 1 g:4-6 mL.

5. The preparation method according to claim 3 or 4, characterized in that: The rotation speed of the ball mill is 50 to 400 rpm, and the time of the ball mill is 0.5 to 36 hours.

6. The preparation method according to claim 3, characterized in that: The mass concentration of the ethanol aqueous solution is above 95%; The mass percentage of the silane coupling agent in the alkylation modification solution is 0.1-20%.

7. The preparation method according to claim 3 or 6, characterized in that: The average diameter of the alumina microspheres is 100 nm to 50 μm; The mass ratio of the alumina microspheres to the alkylsilane coupling agent is 0.1 to 10:

1.

8. The preparation method according to claim 3, characterized in that: The temperature of the heating treatment is 20-100° C., and the time is 0.5-20 hours.

9. The preparation method according to claim 3, characterized in that: The mass ratio of the hydroxylated hexagonal boron nitride nanosheets to the alkylated alumina microspheres is 0.1 to 10:1; The coating is accompanied by stirring, the stirring is magnetic stirring, and the time of the magnetic stirring is 0.5 to 20 hours.

10. Use of the modified hexagonal boron nitride composite according to claim 1 or 2 or the modified hexagonal boron nitride prepared by the preparation method according to any one of claims 3 to 9 as a thermal conductive filler.

Citation Information

Cited By

  • Heat-conducting composite material as well as preparation method and application thereof

    CN121673760A

  • PP-based battery cell lead terminal material containing modified insulating heat-conducting filler and preparation method of PP-based battery cell lead terminal material

    CN122302424A